2018
DOI: 10.1038/s41598-018-29392-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon analysis of modern olive wood raises doubts concerning a crucial piece of evidence in dating the Santorini eruption

Abstract: Charred olive wood is abundant in the archaeological record, especially around the Mediterranean. As the outermost ring closest to the bark is assumed to represent the latest time that the tree was alive, the radiocarbon date obtained from the outermost rings of an olive branch buried during the Santorini volcanic eruption is regarded as crucial evidence for the date of this cataclysmic event. The date of this eruption has far reaching consequences in the archaeology of the Aegean, Egypt and the Levant, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Very recently, new insights on the matter have been revealed. First, the validity of olive trees for wiggle match dating was questioned (Ehrlich et al 2018). This is not further discussed here.…”
Section: The Minoan Santorini (Thera) Eruptionmentioning
confidence: 99%
“…Very recently, new insights on the matter have been revealed. First, the validity of olive trees for wiggle match dating was questioned (Ehrlich et al 2018). This is not further discussed here.…”
Section: The Minoan Santorini (Thera) Eruptionmentioning
confidence: 99%
“…Both these applications demonstrate how annual 14 C can be used to anchor floating living and subfossil tree-ring chronologies and thus fill in some of the temporal and geographic gaps we have discussed in this review. It may also be used to assist in the better dating of ring-less species (Ehrlich et al, 2018) and the extended potential is clear as these markers continue to be identified in other proxy records such as corals (Ding et al, 2015; Liu et al, 2014). Annual 14 C in tree-ring series is therefore a rapidly expanding area for new research and an area which exemplifies the power of annually dated tree rings and the ‘tree-ring time capsule’ for cross-disciplinary research.…”
Section: Annual 14cmentioning
confidence: 99%
“…However, two recent developments (Pearson et al, 2018;Ehrlich et al, 2018) necessitate a reassessment of the above 14 C date of the Minoan Santorini eruption. Concerning olive wood, Ehrlich et al (2018) measured radiocarbon concentrations in a modern olive tree trunk and a living olive tree branch. They obtained near-annual resolution dates using the radiocarbon "bomb peak".…”
Section: Regional Settingmentioning
confidence: 99%
“…Concerning calibration of radiocarbon dates into calendar years, Pearson et al (2018) published detailed 14 C measurements of annual tree rings from California and Ireland for the period 1700-1500 BCE, dated by dendrochronology. Their results show a distinct departure from the present calibration curve IntCal13 (Reimer et al, 2013).…”
Section: Regional Settingmentioning
confidence: 99%